Deformation Properties ECC Incorporating Crumb Rubber and Nano-Silica - Mohd Yazid, Nurfarahana (IRC, 2019)
Engineered Cementitious Composite (ECC) is a class of high-performance fibre reinforced cement based composite (HPFRCC) that exhibits strain hardening and multiple cracking behaviour under tension and bending. This is a relatively new material in the construction industry and research on its possible applications is still in progress.